MENGENAL TAREKAT DI DUNIA ISLAM - Yuslia Styawati (Program Studi Ilmu Tasawuf IAI Pangeran Diponegoro Nganjuk, Jawa Timur, 2020)
Sufi orders have been instrumental in the life of the Sufis as centers for spiritual training and education. In these centers the Sufis can elaborate their ideas, and apply them in real life. In the passages of time however, these orders were no longer considered simply as religious centers but also as sufis grouping consisting of people committed to practice the teaching of their religion.This article tries to describes these sufis grouping and their doctrins. Such as Qadiriah, Syadziliyah and Syattariyah.